Communicating pain: emerging axonal signaling in peripheral neuropathic pain - Livia Testa; Livia Testa; Sofia Dotta; Sofia Dotta; Alessandro Vercelli; Alessandro Vercelli; Letizia Marvaldi; Letizia Marvaldi (Frontiers Media S.A., 2024)
Peripheral nerve damage often leads to the onset of neuropathic pain (NeuP). This condition afflicts millions of people, significantly burdening healthcare systems and putting strain on families' financial well-being. Here, we will focus on the role of peripheral sensory neurons, specifically the Dorsal Root Ganglia neurons (DRG neurons) in the development of NeuP. After axotomy, DRG neurons activate regenerative signals of axons-soma communication to promote a gene program that activates an axonal branching and elongation processes. The results of a neuronal morphological cytoskeleton change are not always associated with functional recovery. Moreover, any axonal miss-targeting may contribute to NeuP development. In this review, we will explore the epidemiology of NeuP and its molecular causes at the level of the peripheral nervous system and the target organs, with major focus on the neuronal cross-talk between intrinsic and extrinsic factors. Specifically, we will describe how failures in the neuronal regenerative program can exacerbate NeuP.